Women's rescuers network: Community support for self-managed abortion in Argentina - Gabriela Luchetti; Valeria Albardonedo; María Victoria Alfonso (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2024)
The availability of medications to induce abortion, especially in contexts of restricted access, has transformed practices and allowed women and/or their community organizations to assist other women in obtaining abortions, whether or not they interact with the healthcare system. This study recovers the experience of a feminist community organization that, from the province of Neuquén, extends throughout the country, creating a network of community care. An exploratory descriptive study with a qualitative approach was conducted to analyze the experiences of women who facilitate access to permitted abortion in Argentina. Through in-depth interviews with three leaders of the feminist collective La Revuelta and semi-structured interviews with 33 members of the socorrista groups, conducted between November 2019 and December 2020, we describe their history and processes of work and growth; we explore their motivations and feelings and characterize the interactions of these organizations with public and private health systems. The results of this work align with the international conversation and bibliographic production about these organizations and their particularities, and with the need to incorporate these forms of care into institutional health systems.